Developing mathematics worksheet using futsal context for school literacy movement - Effendi, Kiki Nia Sania; Zulkardi; Putri, Ratu Ilma Indra; Yaniawati, Poppy (Journal on Mathematics Education, 2019)
School Literacy Movement, one of the government's efforts to optimize the ability of students in terms of literacy, needs support from every circle; one of them is from researches in the educational field. This research aims to develop reading texts in a futsal context that will be presented in students’ worksheet with valid and practical criteria that will have a potential effect in mathematics learning. This research is using the design research method with a development studies type that consists of three main steps, such as preliminary, prototyping, and assessment with an evaluation plot formative study that used in a prototyping step, including the self-evaluation, expert review and one-to-one, small group, and field test. The research subjects are the students in 7th grade in one of Junior High School in Karawang. There are some steps taken in the data collection process, such as documentation, walkthrough, questionnaire, test, and interview. According to the data analysis, it can be concluded that this research has been producing a product in the form of thirteen reading the text for School Literacy Movement invalid and practical mathematics learning that will have a potential effect for the students’ learning result in the mathematics learning process.